Parental treatment methods and their relationship to social intelligence on a sample of adolescents and adolescents in the town of Beit Hanina - AL-Bahar, Hanin Ali Hasan; Sondoqah, Yasmeen “Mohammad Fathi” Abed Alfattah (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the method of parental treatment and its relationship to social intelligence in a sample of adolescents and adolescents in the town of Beit Hanina. To achieve this goal، the descriptive method was used by applying a questionnaire consisting of two sections، the first section of the methods of parental treatment consisting of (24) paragraphs، and the measure of social intelligence (21) paragraphs، the sample of the study consisted of adolescents and adolescents of the town of Beit Hanina، where they numbered (113). The results of the study found that there are no statistically significant differences at the level of indication. There are no statistically significant differences between parental treatment methods and social intelligence attributable to the variable sex، the variable number of brothers and sisters، the variable age group، the variable of the scientific qualification of the father and the scientific qualification of the mother، but There are statistically significant differences at the level in parental treatment methods and social intelligence due to the change of the person responsible for the adolescent. The study found that the methods of parental treatment were closer to leniency، if the average arithmetic (3.67)، and then the democratic style، and the authoritarian style. The degree of social intelligence was low and averaged 2.30. In the light of these results، the researchers recommended a number of recommendations، the most important of which are: the preparation of awareness programs and guidance for parents by educational specialists to explain the importance of the method used in raising children using the best positive methods and avoiding negative methods that may lead children to a decrease in Social intelligence. To guide the attention of officials in the field of psychological guidance to the importance of social intelligence and methods of parental treatment in the preparation of programs and training courses aimed at developing social intelligence among students، and spreading educational awareness.